Sugar Intake among Preschool-Aged Children in the Guelph Family Health Study: Associations with Sociodemographic Characteristics - Anisha Mahajan; Jess Haines; Jessica Yu; Gerarda Darlington; Andrea C. Buchholz; Alison M. Duncan; David W. L. Ma; on behalf of the Guelph Family Health Study (MDPI AG, 2023)
Background: It is crucial to develop strategies targeted to promote healthy eating patterns in vulnerable populations, especially young children from diverse sociodemographic groups. Thus, the study objective was to investigate the associations between child age, child sex, child ethnicity, parent number of years living in Canada, annual household income, parent education and parent marital status with total, free and added sugar intakes in young children. Methods: This cross-sectional study was a secondary analysis of data gathered in the Guelph Family Health Study. The study included 267 children (129M; 138F) from 210 families aged 1.5 to 5 years. Parents completed questionnaires for children on sociodemographic characteristics and an online 24-hour diet recall. The associations between sociodemographic characteristics and sugar intakes were determined using generalized estimating equations applied to linear regression models. Results: The mean age of the children was 3.5 ± 1.2 years (mean ± std dev.). As children's age increased, there was a greater intake of free and added sugar (<semantics><mover accent="true">β^</mover></semantics> = 8.6, p = 0.01, 95% CI = 2.4 to 14.7 and <semantics><mover accent="true">β^</mover></semantics> = 6.5, p = 0.03, 95% CI = 0.8 to 12.2, respectively). Those children who identified as white had a higher total sugar intake than children of other ethnicities (<semantics><mover accent="true">β^</mover></semantics> = 31.0, p = 0.01, 95% CI = 7.2 to 54.7). Additionally, higher annual household income was associated with lower was free sugar intake in children (<semantics><mover accent="true">β^</mover></semantics> = −2.4, p = 0.02, 95% CI = −4.5 to −0.4). Conclusions: This study underscores the significant influence of multiple sociodemographic characteristics on sugar intake in young children, providing valuable insights for public health policy and nutrition interventions. Moreover, this study highlights the need for early behaviour interventions focusing on reducing sugar intake in young children, while considering sociodemographic factors.